2009
DOI: 10.1016/j.jvs.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical repair of a congenital aneurysm of the distal abdominal aorta in a newborn

Abstract: Congenital (primary) neonatal abdominal aortic aneurysm (AAA) is an extremely rare truncular arterial abnormality among numerous congenital vascular malformations. Only seven cases have been reported as congenital origin in newborns. This report presents the case of a male infant in whom a 33-mm congenital AAA was diagnosed prenatally and was successfully treated 10 days after birth without exogenous graft material or aneurysmorrhaphy. Follow-up study at 39 months demonstrated excellent clinical, ultrasound sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…[7] Although there has not been any study comparing individual surgical approaches in CAAA, aneurysmorrhaphy has been found to have higher recurrence rate. [8] Among the 26 cases reported so far, surgical correction could not be done in 11 (42%) patients due to late presentation, extensive involvement, renal dysfunction, or rupture of aneurysm during exploration. Of these 11, six either died in theater or in early follow-up after surgery (<1 month).…”
Section: Discussionmentioning
confidence: 99%
“…[7] Although there has not been any study comparing individual surgical approaches in CAAA, aneurysmorrhaphy has been found to have higher recurrence rate. [8] Among the 26 cases reported so far, surgical correction could not be done in 11 (42%) patients due to late presentation, extensive involvement, renal dysfunction, or rupture of aneurysm during exploration. Of these 11, six either died in theater or in early follow-up after surgery (<1 month).…”
Section: Discussionmentioning
confidence: 99%
“…In the present review, reconstruction of AAA was achieved using native vessels without exogenous material in a 10-day-old boy [ 23 ]. This method was feasible, allowed natural vessel growth, and avoided graft-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have advocated against the use of cryopreserved human allografts in children given their lack of growth potential and propensity to evoke an immune reaction with subsequent fibrosis, degradation, and propensity for aneurysm formation as chief concerns. 20 Adult data have demonstrated, however, that use of cryopreserved human allografts in the setting of infection carries similar mortality risk and serves as a functional alternative to vascular reconstruction in patients without adequate autogenous conduit 21 dof which children would be a prime example. Others have also recommended use of cryopreserved vascular conduits in children under 6 years of age because of anatomic limitations on vessel size.…”
Section: Discussionmentioning
confidence: 99%